2020
DOI: 10.1177/1526924819893285
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Core Variables Associated With Health Literacy in Kidney Transplant Recipients

Abstract: Background: A kidney transplantation requires complex self-care skills and adequate follow-up from health-care providers. Identifying strengths and limitations in different aspects of health literacy (HL) and associated variables are central to being able to improve health care. The objective of this study was to identify core variables associated with independent domains of HL 8 weeks following a kidney transplantation. Methods: A single-center cross-sectional study was conducted, wherein 159 kidney transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 118 publications
(155 reference statements)
0
11
1
1
Order By: Relevance
“…In contrast to other studies measuring self-reported HL in persons looking after their own health [13,26,45], we found that the parents reported an overall high ability to manage their child's health. This result may indicate that the parents were highly motivated and capable of trying to provide the best available health service to their child, which is an important starting point to receive health information and guidance.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to other studies measuring self-reported HL in persons looking after their own health [13,26,45], we found that the parents reported an overall high ability to manage their child's health. This result may indicate that the parents were highly motivated and capable of trying to provide the best available health service to their child, which is an important starting point to receive health information and guidance.…”
Section: Discussioncontrasting
confidence: 99%
“…We can hypothesize in line with Lee et al 28 that the partner might influence health-related decisions and might assimilate and digest information, just like the patient. 29 Other studies suggest that social contacts might be an important source of medical information. 30 When looking at the concept of HL, this phenomenon is called distributed literacy by Edwards et al 31 and emphasizes the positive influence of social support on HL and healthrelated behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in accordance with recent literature. 29,32 While a language barrier is a prominent aspect hindering patients from acquiring sufficient knowledge or from understanding the questions on a self-rating instrument correctly, other reasons might be of importance as well. Schouten et al 33 suggest that cultural differences can influence the patients' • Before intake 93.7%…”
Section: Discussionmentioning
confidence: 99%
“…Of the six studies that used the HLQ (see Table S4), the highest scores were obtained for the domains 'healthcare provider support' (Dahl et al, 2020;Demian et al, 2016;Dodson et al, 2016;Stømer et al, 2019), 'social support' (Griva et al, 2020;Skoumalova et al, 2019) and 'active engagement' (Dahl et al, 2020;Dodson et al, 2016;Griva et al, 2020;Skoumalova et al, 2019;Stømer et al, 2019). The lowest scores were obtained for the domains 'critical appraisal' (Dahl et al, 2020;Demian et al, 2016;Dodson et al, 2016;Griva et al, 2020;Skoumalova et al, 2019;Stømer et al, 2019), 'finding good health information' (Demian et al, 2016;Dodson et al, 2016;Griva et al, 2020;Stømer et al, 2019), and 'navigating the healthcare system' (Dahl et al, 2020;Skoumalova et al, 2019). Lambert et al (2015), using the HeLMS found that individuals had lower scores for domains 'attitudes towards their health' and 'socioeconomic factors'.…”
Section: Health Literacymentioning
confidence: 99%
“…One study examined the relationship between health literacy and transplantation knowledge (Dahl et al, 2020) and found that higher knowledge scores were associated with greater health literacy (see Table S6). Knowledge was the driving factor for the domains 'healthcare provider support' and 'understanding of health information'.…”
Section: Health Literacy and Knowledgementioning
confidence: 99%